On the stability of the RuCl2(triphenylphosphine)(2)(amine) complexes: Ligand substituent effects of cyclic and acyclic amines - Viana, Rommel B.; Souza, Aguinaldo Robinson de [UNESP]; Lima-Neto, Benedito S.; Silva, Alberico B. F. da (Elsevier B.V., 2014)
In this investigation we applied the Density Functional Theory to understand the substituent effects of cyclic and acyclic amines on the stability of RuCl2(PPh3)(2)(amine) complexes. In order to evaluate the relative stability of each complex, we analyzed five conformations considering different positions of the chlorine atoms and the triphenylphosphine ligand: a cis-cis (1), a trans-trans (2), a trans-cis (3), a cis-cis (4) and a cis-trans configuration (5). In addition, eight different amine ligands were considered: two acyclic (ammonia and trimethylamine), two cyclic aliphatic (piperidine and pyrrolidine) and four aromatic amine ligands (pyridine, pyrazine, pyrimidine and pyridazine). All the structures presented a square pyramid geometry, and in all systems the stereoisomer 3 is the most stable arrangement among the five isomers. Among the complexes with cyclic aliphatic amine ligands, the energy gap between arrangements 2 and 3 are the most sensitive to the substituent change. Furthermore, when it is considered the replacement by an aromatic amine, there are a large decrease in the energy difference between the arrangements 2 and 3. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Ruthenium complexes; NBO; Reactivity; Charge distribution; Vibrational frequencies